Recycled aggregate cement stabilized macadam subbase design method based on grading recombination
By improving the aggregate crushing technology and water washing method, the initial target grading of synthetic recycled aggregates is solved, and the problems of high yield and low utilization efficiency of recycled aggregates are achieved, and the design of stable cement gravel base layer is achieved, reducing energy consumption And improve construction efficiency.
Patent Information
- Application Number
- CN202411695805.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high yield of recycled aggregates, the storage occupies land resources, low utilization efficiency, and the large energy consumption of mechanical grinding and high temperature methods affects its performance.
The design method of recycled aggregate cement stabilized gravel base layer based on graded recombination is adopted. The technical parameters of aggregate crushing are improved through the evaluation and verification indicators of working performance, and the recycled aggregate is collected in batches, and aggregates that meet the requirements of the specifications are screened, and water-washed is used. The method was used to perform screening, synthesize the initial target grading, conduct heavy-duty strike test and 7-d unlimited compressive strength test to determine the mix ratio and cement dosage.
It improves the utilization efficiency of recycled aggregates, reduces energy consumption, solves the problem of long-term crushing and heavy screening on-site construction, and realizes the design of cement-stabilized gravel base base layer that complies with the specifications.
Smart Images

Figure CN119296701A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cement concrete pavement design, and in particular relates to a recycled aggregate cement stabilized crushed stone subbase design method based on grading reorganization. Background Art
[0002] In the highway industry, the recycling of waste concrete is an important part of the entire life cycle of highways and a key link in achieving resource conservation and energy conservation and emission reduction in the field of engineering construction. At present, the demand for concrete is increasing day by day, and the corresponding demand for sand and gravel is also increasing sharply. However, natural sand and gravel resources are limited, high-quality natural aggregates are close to exhaustion in some areas of my country, the supply of qualified sand and gravel is relatively tight, and excessive mining will damage the natural environment. Recycled concrete uses crushed waste concrete as recycled aggregate to partially or completely replace natural aggregates to prepare green concrete. The use of recycled aggregates can not only avoid the ecological damage caused by the random stacking of waste concrete and the excessive mining of natural aggregates, but also effectively recycle and utilize waste resources, so it has very important ecological, economic and social significance. However, problems such as porosity, high water absorption, and low strength affect the performance of recycled aggregate concrete. Removing the slurry attached to the surface of recycled aggregates is the key to improving its performance. At present, mechanical grinding and high temperature methods are usually used to remove slurry, which consumes a lot of energy and brings energy consumption problems. Summary of the invention
[0003] In order to solve the problems of high output of recycled aggregate, land resource occupation by stockpiling, and low efficiency of high-value utilization, the present invention proposes a recycled aggregate redistribution coefficient, reorganizes the grading of the crushed recycled aggregate, and partially replaces natural aggregate to design a cement-stabilized crushed stone subbase.
[0004] To achieve the above object, the present invention provides a method for designing a recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization, comprising:
[0005] Improve the aggregate crushing technical parameters based on the evaluation and verification indicators of working performance, and then collect the recycled aggregate in different grades;
[0006] Determine whether the recycled aggregate meets the requirements of the technical specifications for cement stabilized crushed stone base construction for the aggregate specifications of the base and subbase, and select and obtain recycled aggregate that meets the requirements;
[0007] The recycled aggregate and primary aggregate meeting the specified requirements are screened by a water washing method, and the initial target gradation of the recycled aggregate is synthesized according to the upper and lower limit ranges of each grade of aggregate recommended by the specification to obtain a recycled aggregate cement-stabilized crushed stone mixture;
[0008] Conducting a heavy compaction test and a 7d unconfined compressive strength test on the recycled aggregate cement-stabilized crushed stone mixture to obtain test results;
[0009] The mix ratio of recycled aggregate cement-stabilized crushed stone subbase is determined based on the test results, and the cement dosage required for the design is obtained according to the mix ratio.
[0010] Preferably, the process of improving aggregate crushing technical parameters based on the evaluation and verification indicators of working performance includes:
[0011] The improvement measures for the primary crushing jaw crusher PE400×600 include: setting the minimum feed particle size ≥300mm and not exceeding 700mm; the discharge diameter is 50~65mm; the operating frequency of the movable jaw is 80~120 times / min.
[0012] The improvement measures for the secondary crushing hammer crusher PC1000×800 include: setting the discharge diameter to 40-55mm; the rotation speed to 700-900r / min; and the number of hammers to 28-32.
[0013] Preferably, the process of collecting the recycled aggregate in grades comprises:
[0014] After the recycled aggregate is crushed by the primary jaw crusher and the secondary hammer crusher in sequence, the recycled aggregate is collected and wood chips, glass and metal impurities are removed, and then sieved to obtain multi-level recycled aggregate;
[0015] The multi-grade recycled aggregate includes but is not limited to recycled aggregates with specifications of 26.5-31.5mm, 19-26.5mm, 9.5-19mm, 4.75-9.5mm, 2.36-4.75mm, 0.6-2.36mm and 0.075-0.6mm.
[0016] Preferably, the process of screening and obtaining recycled aggregates that meet the specified requirements includes:
[0017] Determine whether the recycled aggregate meets the requirements of the technical specifications for cement stabilized crushed stone base construction for the aggregate specifications of the base and subbase. If it meets the requirements, classify the recycled aggregate according to the nominal particle size;
[0018] If it does not meet the specified requirements, for single-specification aggregates whose nominal particle size composition does not meet the preset requirements, the key sieve hole pass rate of aggregates of different specifications shall be controlled within the standard grading deviation range, so that the key sieve hole deviation range meets the preset allowable deviation range of the single-specification aggregate grading.
[0019] Preferably, the process of screening the recycled aggregate and the primary aggregate that meet the specified requirements by the water washing method includes:
[0020] The recycled aggregate and the original aggregate that meet the specified requirements are screened by a water washing method, and the aggregate performance indicators of the recycled aggregate and the original aggregate are tested;
[0021] Among them, the aggregate performance indicators include but are not limited to density, crushing value, water absorption rate, mud content, sand equivalent, and needle-like content.
[0022] Preferably, the process of synthesizing the initial target gradation of recycled aggregate according to the upper and lower limits of each grade of aggregate recommended by the specification includes:
[0023] According to the average screening curve of each grade of aggregate, the target gradation is synthesized, the usage ratio is determined, and the synthetic gradation of the mixture is obtained;
[0024] Carry out a heavy compaction test and a 7d unconfined compressive strength test of the mixture according to the synthetic gradation to verify the performance of the mixture;
[0025] Obtaining an ideal parabolic maximum density curve of the particle gradation of the uncrushed water-stabilized mixture, and obtaining a relationship expression between aggregates of various grades according to the ideal parabolic maximum density curve;
[0026] The initial gradation of recycled aggregate cement stabilized crushed stone is calculated based on the relationship expression between the various grades of aggregate.
[0027] Preferably, the relationship between the various aggregates is expressed as:
[0028]
[0029] Where: P x It is the passing percentage of aggregate with a certain particle size d, in %; D is the maximum particle size of the aggregate, in mm.
[0030] Preferably, the process of performing a heavy compaction test on the recycled aggregate cement-stabilized crushed stone mixture comprises:
[0031] The recycled aggregate after dry screening is subjected to heavy compaction test, and cement with a moisture content of 8% and 3.5% is added according to the state. After the heavy compaction test, it is immediately washed with water, dried and then screened;
[0032] According to the changes in the passing rate of each aggregate level before and after heavy compaction, each aggregate level is recalculated and the changes in each aggregate level are statistically analyzed to obtain the changes in each aggregate level of recycled aggregate cement stabilized crushed stone:
[0033] When the recycled aggregate is crushed, the gradation is reorganized. The passing rate of each aggregate level in the original gradation is defined as α1-α8. The passing rate of each aggregate level after heavy compaction is X1-X7. The gradation change of the recycled aggregate after crushing is expressed according to the calculation formula.
[0034] Preferably, the calculation formula for expressing the change in gradation of recycled aggregate after crushing includes:
[0035] β 11 x1=α1
[0036] β 21 x1+β 22 x2=α2
[0037] β 31 x1+β 32 x2+β 33 x3=α3
[0038] β 41 x1+β 42 x2+β 43 x3+β 44 x4=α4
[0039] β 51 x1+β 52 x2+β 53 x3+β 54 x4+β 55 x5=α5
[0040] β 61 x1+β 62 x2+β 63 x3+β 64 x4+β 65 x5+β 66 x6=α6
[0041] β 71 x1+β 72 x2+β 73 x3+β 74 x4+β 75 x5+β 76 x6+β 77 x7=α7
[0042] Among them, β ij is the crushing coefficient of each grade of aggregate after crushing and re-screening of recycled aggregate, i represents the passing particle size of recycled aggregate, i=1 corresponds to the passing particle size of 26.5mm; j represents the proportion of aggregate after crushing by the jth grade, X i It indicates the passing rate of each grade of recycled aggregate after heavy compaction, α i It indicates the passing rate of each grade of recycled aggregate before heavy compaction.
[0043] Preferably, the process of conducting a 7-day unconfined compressive strength test on the recycled aggregate cement-stabilized crushed stone mixture comprises:
[0044] According to the compaction test results, φ150mm×150mm cylindrical specimens were made to make cement-stabilized crushed stone specimens, with the compaction degree controlled at 98%, and static pressure molding, with 1% redundancy considered during molding;
[0045] The static pressure formed specimens are subjected to standard curing for 6 days at a temperature of 20℃±2℃ and a humidity of more than 95%. The specimens are immersed in water for 1 day before testing the compressive strength. The specimens are cured to the age of 7 days and then tested by unconfined compressive strength test in accordance with the test procedures for inorganic binder stabilized materials.
[0046] Compared with the prior art, the present invention has the following advantages and technical effects:
[0047] The invention proposes a classification crushing coefficient, and can predict the re-gradation of recycled aggregate, thereby solving the problem of time-consuming crushing and re-screening in on-site construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0049] Figure 1 A schematic diagram of a method flow chart of an embodiment of the present invention;
[0050] Figure 2 1 is a moisture content-dry density relationship curve diagram of an embodiment of the present invention. DETAILED DESCRIPTION
[0051] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0052] It should be noted that the steps shown in the flowcharts of the accompanying drawings can be executed in a computer system such as a set of computer executable instructions, and that, although a logical order is shown in the flowcharts, in some cases, the steps shown or described can be executed in an order different from that shown here.
[0053] The production and processing of recycled aggregates is still mainly based on ordinary crushers. In order for recycled aggregates produced from waste concrete to meet road use requirements, they need to go through the process of removing reinforcement, sorting, pre-crushing, crushing, screening, etc., among which the most critical link is crushing. After pre-crushing, the aggregates are graded through screens to obtain aggregates of different particle sizes, but the current instruments and equipment have problems such as complicated processes and processing equipment.
[0054] The essence of recycled aggregates is different from ordinary natural aggregates in that the surface of the aggregates is coated with mortar or the aggregates themselves contain mortar blocks. It is precisely because of the existence of these mortars that the performance of recycled aggregates has shown significant differences, mainly manifested in the characteristics of high crushing value, water absorption rate, water absorption rate, and low density.
[0055] In order to solve the above problems, this embodiment proposes a method for improving the technical parameters of aggregate crushing, and further improves the performance of recycled aggregate through carbonization.
[0056] like Figure 1-2 As shown, this embodiment provides a method for designing a recycled aggregate cement-stabilized crushed stone subbase based on grading reorganization, comprising the following steps:
[0057] Improve the aggregate crushing technical parameters based on the evaluation and verification indicators of working performance, and then collect the recycled aggregate in different grades;
[0058] Determine whether the recycled aggregate meets the requirements of the technical specifications for cement stabilized crushed stone base construction for the aggregate specifications of the base and subbase, and select and obtain recycled aggregate that meets the requirements;
[0059] The recycled aggregate and primary aggregate meeting the specified requirements are screened by a water washing method, and the initial target gradation of the recycled aggregate is synthesized according to the upper and lower limit ranges of each grade of aggregate recommended by the specification to obtain a recycled aggregate cement-stabilized crushed stone mixture;
[0060] Conducting a heavy compaction test and a 7d unconfined compressive strength test on the recycled aggregate cement-stabilized crushed stone mixture to obtain test results;
[0061] The mix ratio of recycled aggregate cement-stabilized crushed stone subbase is determined based on the test results, and the cement dosage required for the design is obtained according to the mix ratio.
[0062] Furthermore, measures to improve technical parameters based on performance evaluation and verification indicators include:
[0063] Improvement measures for the primary crushing jaw crusher (PE400×600): set the minimum feed particle size ≥300mm and not more than 700mm; the discharge diameter is 50~65mm; the operating frequency of the movable jaw is 80~120 times / min.
[0064] Improvement measures for secondary hammer crusher (PC1000×800): discharge diameter is 40-55mm; rotation speed is 700-900r / min; number of hammers is 28-32.
[0065] The main purpose of the secondary hammer crusher after the primary jaw crusher is to ensure aggregates with a certain particle size and clean surface, while reducing the amount of micro cracks on the aggregate surface and over-crushed aggregates.
[0066] Further, the collection of recycled aggregates includes: performing primary jaw crushing and secondary hammer crushing on the recycled aggregates in sequence by a primary crushing jaw crusher and a secondary crushing hammer crusher, collecting the recycled aggregates, removing wood chips, glass, metal impurities, etc., crushing them by the jaw crusher, and then sieving and screening to obtain multi-grade recycled aggregates, which are recycled aggregates with specifications of 26.5-31.5 mm, 19-26.5 mm, 9.5-19 mm, 4.75-9.5 mm, 2.36-4.75 mm, 0.6-2.36 mm and 0.075-0.6 mm;
[0067] The present invention is based on recycled aggregate collected in grades and is applied to the design of a recycled aggregate cement stabilized crushed stone subbase:
[0068] (1) Material selection: The selected materials mainly include P·O42.5 slow-setting cement, and the aggregates include recycled aggregates with specifications of 26.5-31.5 mm, 19-26.5 mm, 9.5-19 mm, 4.75-9.5 mm, 2.36-4.75 mm, 0.6-2.36 mm, and 0.075-0.6 mm;
[0069] According to the requirements of DB37-T3577-2019 Technical Specifications for Construction of Cement Stabilized Crushed Stone Base for the aggregate specifications of base and subbase, it shall comply with the aggregate specifications in Table 1.
[0070] Table 1
[0071]
[0072]
[0073] When the particle size composition of a single-specification aggregate does not meet the requirements of Table 1, in order to ensure the stability of the aggregate gradation and ensure that the fluctuation range of the synthetic gradation of the mixture is within the allowable deviation range, the pass rate of the key sieve holes of aggregates of different specifications is controlled according to the standard gradation deviation range, and the allowable deviation range of the key sieve holes is in accordance with the allowable deviation range of the single-specification aggregate gradation specified in Table 2.
[0074] Table 2
[0075]
[0076] (2) Gradation design: Take the recycled aggregate and the original aggregate and place them in an oven at 105±5℃ to dry them. Weigh the total mass of the dried aggregate. Place the aggregate in a sufficient amount of clean water. The water level should cover all the aggregate. Use a stirring rod to stir the aggregate thoroughly and wash the surface of the aggregate. Be careful not to stir the aggregate out of the container. Repeat the above steps until the poured water is clean, and then sieve the aggregate. And test the aggregate performance indicators such as density, crushing value, water absorption, mud content, sand equivalent, and needle-like content. The initial gradation design refers to the relevant provisions on the gradation range of skeleton dense cement stabilized gravel mixture in DB37-T3577-2019 Technical Specifications for Construction of Cement Stabilized Gravel Base. The upper and lower limits and median values of the gradation range of the skeleton dense cement stabilized gravel mixture are shown in Table 3.
[0077] Table 3
[0078] Screen size (mm) 31.5 26.5 19 9.5 4.75 2.36 0.6 0.075 Upper limit 100 100 86 57 42 28 16 6 Lower limit 100 90 76 43 28 16 8 2 Median 100 95 81 50 35 22 12 4
[0079] (3) According to the upper and lower limits of each grade of aggregate recommended in the above specifications, the initial target gradation of recycled aggregate is synthesized according to the following steps:
[0080] a) synthesizing the target gradation according to the average screening curve of each grade of aggregate, determining the usage ratio, and obtaining the synthetic gradation of the mixture;
[0081] b) Carry out heavy compaction test and 7d unconfined compressive strength test on the mixture according to the synthetic gradation to verify the performance of the mixture.
[0082] c) The particle size distribution of the uncrushed water-stabilized mixture satisfies the ideal curve of parabola maximum density, and the relationship between the aggregates of each grade satisfies the following equation:
[0083]
[0084] Where: P x It is the passing percentage of aggregate with a certain particle size d, in %; D is the maximum particle size of the aggregate, in mm.
[0085] The initial gradation of recycled aggregate cement stabilized gravel is obtained by calculation through a)-c). The initial gradation of recycled aggregate cement stabilized gravel is shown in Table 4.
[0086] Table 4
[0087]
[0088] According to the results in Table 4, corresponding to the requirements in Table 3, the solution in this embodiment meets the requirements specified in the specification. Then, a heavy compaction test and a 7d unconfined compressive strength test were performed on the recycled aggregate cement stabilized crushed stone mixture.
[0089] (4) The recycled aggregate after dry screening was subjected to a heavy compaction test. According to the state, 8% moisture content and 3.5% cement were added. In order to prevent cement coagulation from affecting the screening results, the recycled aggregate was immediately washed with water after the heavy compaction test, and then dried and screened. The heavy compaction reorganization gradation results of the recycled aggregate cement stabilized crushed stone are shown in Table 5:
[0090] Table 5
[0091]
[0092] (5) From the changes in the passing rate of each aggregate level before and after heavy compaction, it can be seen that the gradation of recycled aggregate changes greatly. Formula (1) is no longer accurate in predicting the gradation reorganization, and each aggregate level should be recalculated;
[0093] Through the data in Table 4 and Table 5, the changes in aggregates of each grade are statistically analyzed. The changes in aggregates of each grade of recycled aggregate cement stabilized crushed stone are shown in Table 6:
[0094] Table 6
[0095]
[0096]
[0097] The gradation of recycled aggregate will be reorganized after crushing. The passing rate of each aggregate grade of the original gradation in Table 4 is defined as α1-α8, and the passing rate of each aggregate grade of recycled aggregate after heavy compaction in Table 5 is α1-α8. A calculation formula is established to express the gradation change of recycled aggregate after crushing.
[0098] Remember β ij is the classification and crushing coefficient of each grade of aggregate after the recycled aggregate is crushed and re-screened, where i represents the passing particle size of the recycled aggregate, and when i=1, the corresponding passing particle size is 26.5mm; j represents the proportion of aggregate after crushing from the jth grade, X i The passing rate of each grade of recycled aggregate after heavy compaction, α i It represents the passing rate of each grade of recycled aggregate before heavy compaction. From this, the following formulas (1)-(7) can be obtained:
[0099] β 11 x1=α1 (1)
[0100] β 21 x1+β 22 x2=α2 (2)
[0101] β 31 x1+β 32 x2+β 33 x3=α3 (3)
[0102] β 41 x1+β42 x2+β 43 x3+β 44 x4=α4 (4)
[0103] β 51 x1+β 52 x2+β 53 x3+β 54 x4+β 55 x5=α5 (5)
[0104] β 61 x1+β 62 x2+β 63 x3+β 64 x4+β 65 x5+β 66 x6=α6 (6)
[0105] β 71 x1+β 72 x2+β 73 x3+β 74 x4+β 75 x5+β 76 x6+β 77 x7=α7 (7)
[0106] After each batch of aggregate is crushed, it will be distributed among the aggregates with a particle size smaller than that batch. In order to determine the re-screening situation and β of the i-th batch of aggregate after crushing, ij (i≠j), according to the experimental data, the increase of the screen residue in each level after the aggregate crushing and re-screening of levels D1-D7 is shown in Table 7 below:
[0107] Table 7
[0108]
[0109]
[0110] According to formulas (1)-(7) and the data shown in Tables 4, 5 and 7, β is calculated. 11 -β 77 , calculated as follows:
[0111]
[0112] Fill the calculated data into Table 7 to obtain the classification and crushing coefficient table of recycled aggregate, see Table 8 for details:
[0113] Table 8
[0114] D1 D2 D3 D4 D5 D6 D7 26.5-31.5mm 0.922 / / / / / / 19-26.5mm 0.034 0.843 / / / / / 9.5-19mm 0.022 0.051 0.813 / / / / 4.75-9.5mm 0.014 0.032 0.022 0.793 / / / 2.36-4.75mm 0.004 0.011 0.013 0.013 0.835 / / 0.6-2.36mm 0.003 0.007 0.006 0.013 0.012 0.788 / 0.075-0.6mm 0.001 0.005 0.002 0.004 0.008 0.012 0.761
[0115] (6) The 7-day unconfined compressive strength of the recycled aggregate before and after compaction was measured: Based on the compaction test results, φ150mm×150mm cylindrical specimens were made into cement-stabilized crushed stone specimens, with the compaction degree controlled at 98%. Static pressing was used to form the specimens, and 1% redundancy was considered during the forming process. The static pressing specimens were subjected to standard curing for 6 days (temperature 20℃±2℃, humidity above 95%), and the specimens were immersed in water for 1 day before the compressive strength test. The specimens were cured to 7 days old, and then the unconfined compressive strength test was carried out according to the test procedures for inorganic binder stabilized materials.
[0116] (7) Determination of the mix ratio of recycled aggregate cement-stabilized crushed stone subbase: According to the requirements of DB37-T3577-2019 Technical Specifications for Construction of Cement-stabilized Crushed Stone Base, the representative strength value should be greater than the design strength of 3.0 MPa. At the same time, the appropriate cement dosage should be selected as the cement dosage for mix ratio design based on the design requirements and previous engineering experience, and taking into account issues such as the mixing uniformity of the mixing station. An error of ±0.2% is allowed for on-site mixing.
[0117] Example 1
[0118] like Figure 1-2 As shown, this embodiment provides a method for designing a recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization, comprising:
[0119] Recycled aggregates should be free of wood chips, glass, metal impurities, etc., and after being crushed by a jaw crusher, they are sieved and screened to obtain multi-grade recycled aggregates, which are 26.5-31.5mm, 19-26.5mm, 9.5-19mm, 4.75-9.5mm, 2.36-4.75mm, 0.6-2.36mm and 0.075-0.6mm in specifications, and are named S1-S7 respectively. Cement is Shanshui P·O42.5 slow-setting cement;
[0120] The recycled aggregate and primary aggregate are screened by water washing method, and their density, crushing value, water absorption, mud content, sand equivalent, needle-like content and other performance indicators are tested;
[0121] After testing, the average crushing value of recycled aggregate is 25.7%;
[0122] The water absorption of S1 is 6.1%, the apparent density is 2.685 g / cm3, the mud content is 1.2%, and the needle-like content is 11.1%;
[0123] The water absorption of S2 is 6.3%, the apparent density is 2.683 g / cm3, the mud content is 1.4%, and the needle-like content is 4.8%;
[0124] The water absorption of S3 is 7.1%, the apparent density is 2.680 g / cm3, the mud content is 2%, and the needle-like content is 5.4%;
[0125] The water absorption of S4 is 7.7%, the apparent density is 1.781 g / cm3, and the mud content is 15.4%;
[0126] The water absorption rate of S5 is 8.2%, the apparent density is 1.731g / cm3, and the mud content is 15.7%
[0127] The water absorption of S6 is 8.6%, the apparent density is 1.581 g / cm3, and the mud content is 15.7%;
[0128] The water absorption of S7 is 8.8%, the apparent density is 1.431 g / cm3, and the mud content is 16.4%;
[0129] The design of cement stabilized crushed stone subbase is carried out in the following steps:
[0130] (1) Material selection: The selected materials mainly include P·O42.5 slow-setting cement, and the aggregates include recycled aggregates with specifications of 26.5-31.5 mm, 19-26.5 mm, 9.5-19 mm, 4.75-9.5 mm, 2.36-4.75 mm, 0.6-2.36 mm, and 0.075-0.6 mm;
[0131] According to the requirements of DB37-T3577-2019 Technical Specifications for Construction of Cement Stabilized Gravel Base, the aggregate specifications for the base and subbase must comply with the provisions of Table 9.
[0132] Table 9
[0133]
[0134] When the particle size composition of a single specification aggregate does not meet the requirements of Table 9, in order to ensure the stability of the aggregate gradation and ensure that the fluctuation range of the synthetic gradation of the mixture is within the allowable deviation range, the key sieve hole pass rate of aggregates of different specifications is controlled within the standard gradation deviation range, and the allowable deviation range of the key sieve hole is specified in Table 10.
[0135] Table 10
[0136]
[0137] (2) Gradation design: The recycled aggregate and primary aggregate are screened by water washing method, and the aggregate performance indicators such as density, crushing value, water absorption, mud content, sand equivalent, and needle-like content are tested. The initial gradation design refers to the relevant provisions on the gradation range of skeleton dense cement stabilized crushed stone mixture in DB37-T3577-2019 Technical Specifications for Construction of Cement Stabilized Crushed Stone Base. The upper, lower and median limits of the design gradation range of cement stabilized crushed stone base are shown in Table 11.
[0138] Table 11
[0139] Screen size (mm) 31.5 26.5 19 9.5 4.75 2.36 0.6 0.075 Upper limit 100 100 86 57 42 28 16 6 Lower limit 100 90 76 43 28 16 8 2 Median 100 95 81 50 35 22 12 4
[0140] (3) The initial gradation of the recycled aggregate cement-stabilized crushed stone subbase is obtained based on the upper and lower limits of each grade of aggregate recommended in the specification and screened on site. The initial gradation of the recycled aggregate cement-stabilized crushed stone screened on site is shown in Table 12.
[0141] Table 12
[0142]
[0143] (3) According to the recycled aggregate classification and crushing coefficient table in Table 8, the amount of recycled aggregate in each level is predicted and calculated, and the amount of aggregate in each level is recorded as x i , its expression (8):
[0144]
[0145] The prediction calculation process of each level of aggregate material after crushing is as follows:
[0146]
[0147] According to the calculation results, the reconstructed gradation of the crushed recycled aggregate cement-stabilized crushed stone subbase is obtained, see Table 13.
[0148] Table 13
[0149]
[0150] After checking the amount of aggregates in each grade, if they all meet the requirements of the design gradation range of cement-stabilized crushed stone subbase in Table 11, construction can be carried out. Heavy compaction test is carried out on the recycled aggregates on site. The optimal moisture content and maximum dry density are determined as follows: the stewing time of the recycled aggregate mixture should be 2 hours longer than that of the original aggregate mixture. At the same time, the moisture content of the recycled aggregate is strictly controlled, and the dosage of 3.5% cement is controlled. Heavy compaction tests with different moisture contents are carried out, and the prepared recycled aggregates are poured into the cylinder three times. Each layer is compacted 98 times, and the height of the aggregate after compaction is required not to exceed 5mm from the top surface of the test cylinder. The moisture content of the compacted aggregate is measured and the wet density and dry density of the aggregate after compaction are calculated. Draw a chart with dry density as the ordinate and moisture content as the abscissa. Find the dry density and moisture content of the five soil samples on the graph in turn, and connect them with a smooth curve. The highest point is the maximum dry density, and the corresponding moisture content is the optimal moisture content. Finally, the optimal moisture content and maximum dry density are determined. The results of the heavy compaction test are shown in Figure 2 And Table 14.
[0151] Table 14
[0152] Number of trials 1 2 3 4 5 Dry density ρ(g / cm3) 2.115 2.133 2.130 2.110 2.020 Measured water content W (%) 7.1 8.0 8.6 8.7 9.1
[0153] According to the compaction test results, the 7d unconfined compressive strength test of recycled aggregate water-stabilized mixture is carried out. The steps are as follows:
[0154] a) Specimen preparation: Cement-stabilized crushed stone specimens were prepared using cylindrical specimens of φ150mm×150mm with a compaction degree of 98% and static pressure molding, with 1% redundancy considered during molding;
[0155] b) Curing: Use standard curing methods to place the demoulded specimens in a standard curing room at a temperature of 20°C ± 2°C and a relative humidity of more than 95%. After curing for 6 days, immerse in water for 1 day;
[0156] c) Compressive strength test: After the specimens have been cured to the specified age, an unconfined compressive strength test is carried out according to the test procedures for inorganic binder stabilized materials. The cement dosage is 3.5%. The 7d unconfined compressive strength test results are shown in Table 15.
[0157] Table 15
[0158] Cement dosage (%) 3.5 Strength average R(MPa) 5.6 Strength standard deviation S(MPa) 0.3 Strength deviation coefficient Cv(%) 5.2 R·(1-ZaCv)(MPa) 5.2 Does it satisfy the formula Rd0≥Rd yes
[0159] From the above tests, it can be seen that the representative strength value of the cement dosage of 3.5% is greater than the design strength of 3.0MPa, which meets the design requirements. According to the design requirements and engineering experience, and taking into account the mixing uniformity of the mixing station and other issues, the cement dosage of 3.5% is determined as the cement dosage for this mix design. A cement dosage deviation of ±0.2% is allowed for on-site mixing.
[0160] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for designing recycled aggregate cement-stabilized crushed stone subbase based on grading reorganization, characterized in that: include: Improve the aggregate crushing technical parameters based on the evaluation and verification indicators of working performance, and then collect the recycled aggregate in different grades; Determine whether the recycled aggregate meets the requirements of the technical specifications for cement stabilized crushed stone base construction for the aggregate specifications of the base and subbase, and select and obtain recycled aggregate that meets the requirements; The recycled aggregate and primary aggregate meeting the specified requirements are screened by a water washing method, and the initial target gradation of the recycled aggregate is synthesized according to the upper and lower limit ranges of each grade of aggregate recommended by the specification to obtain a recycled aggregate cement-stabilized crushed stone mixture; Conducting a heavy compaction test and a 7d unconfined compressive strength test on the recycled aggregate cement-stabilized crushed stone mixture to obtain test results; The mix ratio of recycled aggregate cement-stabilized crushed stone subbase is determined based on the test results, and the cement dosage required for the design is obtained according to the mix ratio.
2. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1 is characterized in that: The process of improving aggregate crushing technical parameters based on performance evaluation and verification indicators includes: The improvement measures for the primary crushing jaw crusher PE400×600 include: setting the minimum feed particle size ≥300mm and not exceeding 700mm; the discharge diameter is 50~65mm; the operating frequency of the movable jaw is 80~120 times / min. The improvement measures for the secondary crushing hammer crusher PC1000×800 include: setting the discharge diameter to 40-55mm; the rotation speed to 700-900r / min; and the number of hammer heads to 28-32.
3. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1 is characterized in that: The process of collecting the recycled aggregate in grades includes: After the recycled aggregate is crushed by the primary jaw crusher and the secondary hammer crusher in sequence, the recycled aggregate is collected and wood chips, glass and metal impurities are removed, and then sieved to obtain multi-level recycled aggregate; The multi-grade recycled aggregate includes but is not limited to recycled aggregates with specifications of 26.5-31.5mm, 19-26.5mm, 9.5-19mm, 4.75-9.5mm, 2.36-4.75mm, 0.6-2.36mm and 0.075-0.6mm.
4. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1 is characterized in that: The process of selecting recycled aggregates that meet the requirements of the regulations includes: Determine whether the recycled aggregate meets the requirements of the technical specifications for cement stabilized crushed stone base construction for the aggregate specifications of the base and subbase. If it meets the requirements, classify the recycled aggregate according to the nominal particle size; If it does not meet the specified requirements, for single-specification aggregates whose nominal particle size composition does not meet the preset requirements, the key sieve hole pass rate of aggregates of different specifications shall be controlled within the standard grading deviation range, so that the key sieve hole deviation range meets the preset allowable deviation range of the single-specification aggregate grading.
5. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1, characterized in that: The process of screening the recycled aggregate and the original aggregate that meet the specified requirements by the water washing method includes: The recycled aggregate and the virgin aggregate that meet the specified requirements are screened by a water washing method, and the aggregate performance indicators of the recycled aggregate and the virgin aggregate are tested; Among them, the aggregate performance indicators include but are not limited to density, crushing value, water absorption rate, mud content, sand equivalent, and needle-like content.
6. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1, characterized in that: The process of synthesizing the initial target gradation of recycled aggregate according to the upper and lower limits of each grade of aggregate recommended by the specification includes: According to the average screening curve of each grade of aggregate, the target gradation is synthesized, the usage ratio is determined, and the synthetic gradation of the mixture is obtained; Carry out a heavy compaction test and a 7d unconfined compressive strength test of the mixture according to the synthetic gradation to verify the performance of the mixture; Obtaining an ideal parabolic maximum density curve of the particle gradation of the uncrushed water-stabilized mixture, and obtaining a relationship expression between aggregates of various grades according to the ideal parabolic maximum density curve; The initial gradation of recycled aggregate cement stabilized crushed stone is calculated based on the relationship expression between the various grades of aggregate.
7. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 6, characterized in that: The relationship between the aggregates of each grade is expressed as follows: Where: P x It is the passing percentage of aggregate with a certain particle size d, in %; D is the maximum particle size of the aggregate, in mm.
8. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1, characterized in that: The process of conducting a heavy compaction test on the recycled aggregate cement stabilized crushed stone mixture includes: The recycled aggregate after dry screening is subjected to heavy compaction test, and cement with a moisture content of 8% and 3.5% is added according to the state. After the heavy compaction test, it is immediately washed with water, dried and then screened; According to the changes in the passing rate of each aggregate level before and after heavy compaction, each aggregate level is recalculated and the changes in each aggregate level are statistically analyzed to obtain the changes in each aggregate level of recycled aggregate cement stabilized crushed stone: When the recycled aggregate is crushed, the gradation is reorganized. The passing rate of each aggregate level in the original gradation is defined as α1-α8. The passing rate of each aggregate level after heavy compaction is X1-X7. The gradation change of the recycled aggregate after crushing is expressed according to the calculation formula.
9. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 8, characterized in that: The calculation formula for expressing the gradation change of recycled aggregate after crushing includes: β 11 x1=α1 b 21 x1+b 22 x2=α2 b 31 x1+b 32 x2+b 33 x3=α3 b 41 x1+b 42 x2+b 43 x3+b 44 x4=α4 b 51 x1+b 52 x2+b 53 x3+b 54 x4+b 55 x5=α5 b 61 x1+b 62 x2+b 63 x3+b 64 x4+b 65 x5+b 66 x6=α6 b 71 x1+b 72 x2+b 73 x3+b 74 x4+b 75 x5+b 76 x6+b 77 x7=α7 Among them, β ij is the crushing coefficient of each grade of aggregate after crushing and re-screening of recycled aggregate, i represents the passing particle size of recycled aggregate, i=1 corresponds to the passing particle size of 26.5mm; j represents the proportion of aggregate after crushing by the jth grade, X i It indicates the passing rate of each grade of recycled aggregate after heavy compaction, α i Indicates the passing rate of each grade of recycled aggregate before heavy compaction.
10. The method for designing recycled aggregate cement-stabilized crushed stone subbase based on gradation reorganization according to claim 1, characterized in that: The process of conducting a 7-day unconfined compressive strength test on the recycled aggregate cement-stabilized crushed stone mixture includes: According to the compaction test results, φ150mm×150mm cylindrical specimens were made to make cement-stabilized crushed stone specimens, with the compaction degree controlled at 98%, and static pressure molding, with 1% redundancy considered during molding; The static pressure formed specimens are subjected to standard curing for 6 days at a temperature of 20℃±2℃ and a humidity of more than 95%. The specimens are immersed in water for 1 day before testing the compressive strength. The specimens are cured to the age of 7 days and then tested by unconfined compressive strength test in accordance with the test procedures for inorganic binder stabilized materials.
Citation Information
Cited By
Jaw crusher crushed aggregate grading method and system
CN120412834A
Method and system for crushing aggregate gradation with a jaw crusher
CN120412834B